All art is propaganda : critical essays - Orwell, George, 1903-1950.; Packer, George, 1960- (Orlando, Fla. : Harcourt, 2008)
Collects critical essays written by George Orwell in the 1940s, in which he discusses the work of Charles Dickens, Rudyard Kipling, T. S. Eliot, Salvador Dali, and others; and also covers propaganda, politics, and more.
Charles Dickens -- Boys' weeklies -- Inside the whale -- Drama reviews: The tempest, The peaceful inn -- Film review: The great dictator -- Wells, Hitler and the world state -- The art of Donald McGill -- No, not one -- Rudyard Kipling -- T.S. Eliot -- Can socialists be happy? -- Benefit of clergy: some notes on Salvador Dali -- Propaganda and demotic speech -- Raffles and Miss Blandish -- Good bad books -- The prevention of literature -- Politics and the English language -- Confessions of a book reviewer -- Politics vs. literature: an examination of Gulliver's travels -- Lear, Tolstoy and the fool -- Writers and Leviathan -- Review of The heart of the matter by Graham Greene -- Reflections on Gandhi.
Includes bibliographical references (p. [363]-374).
Kirkus Review.
Library Journal.
Pub Weekly.
Adult
Keywords: English essays